Отношение граждан Украины к ее вступлению в Евросоюз и НАТО и их оценки своей осведомленности об этих организациях - Хмелько, В. (Социология: теория, методы, маркетинг, 2006)
On a basis of data of sampling survey (enveloping 2017 respondents and representative for adult population of Ukraine) attitudes of different categories of population towards the Ukraine’s entry into the European Union and NATO, as well as relationships of these attitudes with opinions of the respondents on their awareness about the European Union and NATO have been analyzed. Those, who regard themselves as better informed about European Union, support Ukraine’s entry into this organization more often than those who consider themselves less informed about it. But in case of NATO such relationship is specific only for the Central Western part of Ukraine. For all country this relationship is neutralized by predominance of opposite relationship in the Southern East part of Ukraine: there, those who consider themselves better inform ed about NATO oppose entry into this organization more often than those who consider they are informed insufficiently.